PENERAPAN PEJABAT (PERMAINAN JUMP, ATTACH, BALANCE AND TWISTS) UNTUK MENINGKATKAN PSIKOMOTORIK DAN KOGNITIF ANAK - Widya Zulfani; Setiati Handayani; Lely Priani (Jurnal Guru Kita PGSD, 2019)
Abstract: The Aplication of PEJABAT (The Games, Jump, Attach, Balance and Twists) to improve children’s psychomotor and cognitive. The purpose of this research was to find out the aplication of PEJABAT in order to see improvement of children’s psychomotor and cognitive through games at Al-Hidayah Kindergarten Starban Street No.46, Medan Polonia. This activity was held for 4 months starting from March to June. The implementation method is carried out, by lecture and simulation methods. There are three ages of implementation. Three of them are the stage of counceling, training and mentoring. The results of this study indicat and proofing the aplication of PEJABAT can improve children’s psychomotor and cognitive in TK Al-Hidayah.Keywords: PEJABAT, Psychomotor, CognitiveAbstrak: Penerapan PEJABAT (Permainan Jump, Attach, Balance And Twist) untuk Meningkatkan Psikomotorik dan Kognitif Anak. Tujuan penelitian ini adalah untuk mengetahui penerapan PEJABAT  terhadap peningkatan psikomotorik dan kognitif anak melalui permainan di TK Al-Hidayah Jalan Starban No.46, Medan Polonia. Kegiatan ini dilaksanakan selama 4 bulan dimulai dari bulan Maret hingga bulan Juni. Metode pelaksanaan kegiatan ini dilaksanakan dengan metode ceramah dan simulasi. Terdapat tiga tahap pelaksanaan yaitu tahap penyuluhan, pelatihan dan pendampingan. Hasil penelitian ini menunjukkan penerapan PEJABAT (Permainan Jump, Attach, Balance and Twist) dapat menisngkatkan psikomotorik dan kognitif anak di TK-Al-Hidayah.Kata Kunci : PEJABAT, Psikomotori, Kognitif.